Fluid intake from beverages in Spanish adults: cross-sectional study - Cíntia Ferreira-Pêgo; Nancy Babio; Juan Miguel Fenández-Alvira; Iris Iglesia; Luis A. Moreno; Jordi Salas-Salvadó (Nutrición Hospitalaria, 2014)
Introduction: Dietary questionnaires usually only assess the intake of drinks that provide calories, but do not accurately evaluate total fluid or water intake. The evaluation of the fluid consumption pattern of a population has been the main objective of only a very few studies. Objective: To evaluate the total fluid intake from different types of beverages in Spanish adults. Methods: A total of 1,262 adults aged 18-70 years were randomly recruited from all Spanish regions. The information about the quantity and quality of daily fluid intake from different types of beverages was collected using a 24h fluid-specific diary over 7 consecutive days. Results: 50.4% of the study population had a fluid intake < 80% of the EFSA recommendations for total water intake. The odds of meeting the recommendations of total fluid intake were higher in women [OR: 2.48; 95%CI: 1.81-3.40], and in those with higher leisure-time physical activity (3-4 times/week [OR: 1.57; 95%CI: 1.012.46]; 5 times/week or more [OR: 1.97; 95%CI: 1.372.83]). Women consumed significantly more hot and sweet light beverages. However, men consumed significantly more sweet regular and alcoholic drinks. A significant higher percentage of young and normal/underweight subjects exceed the WHO recommendations for free sugars (> 10% total energy intake) from beverages alone. Conclusion: Half of the adults studied do not meet the EFSA fluid intake recommendations. Water is the main fluid consumed. Differences in the pattern of fluid consumption were observed between ages and genders. A quarter of the population studied consumes from beverages alone already more sugar than recommended from the total diet.